2016
DOI: 10.3324/haematol.2015.139527
|View full text |Cite
|
Sign up to set email alerts
|

Retroviral insertional mutagenesis identifies the del(5q) genes, CXXC5, TIFAB and ETF1, as well as the Wnt pathway, as potential targets in del(5q) myeloid neoplasms

Abstract: Retroviral insertional mutagenesis identifies the del(5q) genes, CXXC5, TIFAB and ETF1, as well as the Wnt pathway, as potential targets in del(5q) myeloid neoplasmsAn interstitial deletion of the long arm of chromosome 5, del(5q), is a recurring abnormality in myeloid disorders, including myelodysplastic syndromes (MDS), de novo acute myeloid leukemia (AML), and therapy-related myeloid neoplasms (t-MN) comprising therapy-related MDS and AML (t-MDS/t-AML).1 In t-MN, a del(5q) occurs in approximately 40% of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…TIFAB is a gene that is deleted in nearly all reported cases of del(5q) MDS and acute myeloid leukemia (AML). 2,3 As expected, TIFAB expression is significantly lower in CD34 + and BM mononuclear (MNC) cells isolated from MDS patients with del(5q) as compared with cells from MDS patients diploid at chr 5q. Recently we have shown that hematopoieticspecific deletion of Tifab results in progressive BM and blood defects, including aberrant HSPC proportions, altered myeloid differentiation and progressive cytopenia.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…TIFAB is a gene that is deleted in nearly all reported cases of del(5q) MDS and acute myeloid leukemia (AML). 2,3 As expected, TIFAB expression is significantly lower in CD34 + and BM mononuclear (MNC) cells isolated from MDS patients with del(5q) as compared with cells from MDS patients diploid at chr 5q. Recently we have shown that hematopoieticspecific deletion of Tifab results in progressive BM and blood defects, including aberrant HSPC proportions, altered myeloid differentiation and progressive cytopenia.…”
supporting
confidence: 62%
“…2 In a separate study, TIFAB was identified by a retroviral insertional mutagenesis screen as a target in del(5q) myeloid neoplasms. 3 …”
mentioning
confidence: 99%
“…Further verification found that ETF1 could be involved in the development of breast cancer and might serve as a biomarker of the HER2 subtype group [26]. Stoddart et al found that ETF1 could produce potential oncogenic abnormal proteins and may be a potential therapeutic target for myeloid tumors [27]. In addition, Yang et al investigated the mechanism of treating diabetes mellitus and nephropathy with mesenchymal stem cells with bioinformatics analysis, and further identified ETF1 playing a vital role in the process as a DEG [28].…”
Section: Discussionmentioning
confidence: 99%
“…In an independent study, TIFAB was identified by a retroviral insertional mutagenesis screen as a target in del(5q) myeloid neoplasms. 21 Tifab-deficient mice develop mild hematopoietic defects and occasionally BM failure. 11 However, hematopoietic-specific deletion of Tifab and miR-146a together results in a highly penetrant BM failure, which better recapitulates human del(5q) MDS.…”
Section: Functional Evidence Of Innate Immune Signaling Dysregulationmentioning
confidence: 99%